Role of percutaneous mitral valve repair in the contemporary management of mitral regurgitation. Issue 19 (22nd June 2015) - Rana, Bushra S; Calvert, Patrick A; Punjabi, Prakash P; Hildick-Smith, David
Abstract : Percutaneous mitral valve (MV) repair has been performed in over 20 000 patients worldwide. As clinical experience in this technique grows indications for its use are being defined. Mitral regurgitation (MR) encompasses a complex heterogeneous group and its treatment is governed by determining a clear understanding of the underlying aetiology. Surgical MV repair remains the gold standard therapy for severe MR. However in select groups of high-risk surgical patients, a percutaneous approach to MV repair is establishing its role. This review gives an overview of the published data in percutaneous MV repair and its impact on the contemporary management of MR.